2003
DOI: 10.1016/s0896-6273(03)00394-5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Drosophila DEG/ENaC Genes to Salt Taste

Abstract: The ability to detect salt is critical for the survival of terrestrial animals. Based on amiloride-dependent inhibition, the receptors that detect salt have been postulated to be DEG/ENaC channels. We found the Drosophila DEG/ENaC genes Pickpocket11 (ppk11) and Pickpocket19 (ppk19) expressed in the larval taste-sensing terminal organ and in adults on the taste bristles of the labelum, the legs, and the wing margins. When we disrupted PPK11 or PPK19 function, larvae lost their ability to discriminate low concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
199
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(210 citation statements)
references
References 67 publications
4
199
1
1
Order By: Relevance
“…2 B), and the behavioral and electrophysiological responses to water were not different among all DGs␣ strains examined in this study. It is known that salt responses in larvae require amiloride-sensitive channels encoded by ppk11 and ppk19 (Liu et al, 2003), and the low and high concentrations of salt responses do not require G␥1 in adult flies (Ishimoto et al, 2005). These findings together with our results suggest that DGs␣ in non-Gr5a GRNs serves for other signaling than taste or that the non-Gr5a GRNs containing DGs␣ are mechanosensory neurons.…”
Section: Discussionsupporting
confidence: 73%
“…2 B), and the behavioral and electrophysiological responses to water were not different among all DGs␣ strains examined in this study. It is known that salt responses in larvae require amiloride-sensitive channels encoded by ppk11 and ppk19 (Liu et al, 2003), and the low and high concentrations of salt responses do not require G␥1 in adult flies (Ishimoto et al, 2005). These findings together with our results suggest that DGs␣ in non-Gr5a GRNs serves for other signaling than taste or that the non-Gr5a GRNs containing DGs␣ are mechanosensory neurons.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, at least three members of the TRP channels, TRP1, Painless, and TRPL are expressed in bitter neurons in the labellum where they are involved in detection of aversive compounds (Al-Anzi et al, 2006;Kim et al, 2010;Zhang et al, 2013b). Also, several ppk channels are expressed in taste neurons where they are required for relevant taste modalities such as low-salt detection (Liu et al, 2003b) and intraspecific chemical communication in larvae (Mast et al, 2014), and water perception (Cameron et al, 2010) and chemical communication during courtship in adults Lu et al, 2012;Starostina et al, 2012;Thistle et al, 2012;Toda et al, 2012;Vijayan et al, 2014). Finally, DmXR, a receptor homologous to metabotropic glutamate receptors that has lost the ability to bind glutamate (Mitri et al, 2004), may also act as a taste receptor.…”
Section: Chemoreceptors and Gustatory Detectionmentioning
confidence: 99%
“…Some of the proteins listed here have not been confirmed as bona fide receptors yet (see main text for details). #In larvae, low-salt solutions seem to be detected by ppk11 and ppk19 (Liu et al, 2003b). *In larvae, GR43a is the only sugar receptor (Mishra et al, 2013).…”
Section: Male Pheromonementioning
confidence: 99%
“…Pickpocket (ppk), the first subunit to be identified, is involved in locomotive behaviour in fruit fly larvae. Other ppk genes have been implicated in fluid re-distribution (Adams et al, 1998;Liu et al, 2003a), gustatory salt perception (Liu et al, 2003b), and male response to female pheromones . Preliminary analysis of the pea aphid genome has indicated that there are between 23 and 26 ppk genes present with conserved structural features, but low overall sequence similarity.…”
Section: Sodium Channel 60ementioning
confidence: 99%